Equality beyond liberal egalitarianism: Walzer’s contribution to the theory of justice - Haus, Michael (New perspectives on distributive justice, 2019)
Das Kapitel Equality beyond Liberal Egalitarianism: Walzer’s Contribution to the Theory of Justice erschien in New Perspectives on Distributive Justice auf Seite 71.
Gesehen am 20.01.2022